Reviving nuclear power: is the Philippines ready? - Trajano, Julius Cesar Imperial (2022)
Philippine President Duterte has signed an executive order to include nuclear power in the country’s energy mix. However, there are critical preparatory issues that need to be resolved to enhance the country’s nuclear energy development.